DOuble SEquential External Defibrillation for Refractory Ventricular Fibrillation (DOSE VF): study protocol for a randomized controlled trial - Ian R. Drennan; Paul Dorian; Shelley McLeod; Ruxandra Pinto; Damon C. Scales; Linda Turner; Michael Feldman; P. Richard Verbeek; Laurie J. Morrison; Sheldon Cheskes (Trials, 2020)
Abstract Background Despite high-quality cardiopulmonary resuscitation (CPR), early defibrillation, and antiarrhythmic medications, some patients remain in refractory ventricular fibrillation (VF) during out-of-hospital cardiac arrest. These patients have worse outcomes compared to patients who respond to initial treatment. Double sequential external defibrillation (DSED) and vector change (VC) defibrillation have been proposed as viable options for patients in refractory VF. However, the evidence supporting the use of novel defibrillation strategies is inconclusive. The objective of this study is to compare two novel therapeutic defibrillation strategies (DSED and VC) against standard defibrillation for patients with treatment refractory VF or pulseless ventricular tachycardia (pVT) during out-of-hospital cardiac arrest. Research question Among adult (≥ 18 years) patients presenting in refractory VF or pulseless ventricular tachycardia (pVT) during out-of-hospital cardiac arrest, does DSED or VC defibrillation result in greater rates of survival to hospital discharge compared to standard defibrillation? Methods This will be a three-arm, cluster randomized trial with repeated crossover conducted in six regions of Ontario, Canada (Peel, Halton, Toronto, Simcoe, London, and Ottawa), over 3 years. All adult (≥ 18 years) patients presenting in refractory VF (defined as patients presenting in VF/pVT and remaining in VF/pVT after three consecutive standard defibrillation attempts during out-of-hospital cardiac arrest of presumed cardiac etiology will be treated by one of three strategies: (1) continued resuscitation using standard defibrillation, (2) resuscitation involving DSED, or (3) resuscitation involving VC (change of defibrillation pads from anterior-lateral to anterior-posterior pad position) defibrillation. The primary outcome will be survival to hospital discharge. Secondary outcomes will include return of spontaneous circulation (ROSC), VF termination after the first interventional shock, VF termination inclusive of all interventional shocks, and number of defibrillation attempts to obtain ROSC. We will also perform an a priori subgroup analysis comparing rates of survival for those who receive “early DSED,” or first DSED shock is shock 4–6, to those who receive “late DSED,” or first DSED shock is shock 7 or later. Discussion A well-designed randomized controlled trial employing a standardized approach to alternative defibrillation strategies early in the treatment of refractory VF is urgently required to determine if the treatments of DSED or VC defibrillation impact clinical outcomes. Trial registration ClinicalTrials.gov NCT04080986 . Registered on 6 September 2019.